Store-Operated Response in CA1 Pyramidal Neurons Exhibits Features of Homeostatic Synaptic Plasticity - Nassrallah, Wissam (Université d'Ottawa / University of Ottawa, 2015)
Homeostatic synaptic plasticity (HSP) regulates synaptic strength in response to changing neuronal firing patterns. This form of plasticity is defined by neurons’ ability to sense and over time integrate their level of firing activity, and to actively maintain it within a defined range. For instance, a compensatory increase in synaptic strength occurs when neuronal activity is chronically attenuated. However, the underpinning cellular mechanisms of this fundamental neural process remain poorly understood. We previously found that during activity deprivation, HSP leads to an increase in α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic (AMPA) receptor function as well as a shift in subunit composition from Ca2+-impermeable GluA2-containing AMPA receptors to Ca2+-permeable GluA2-lacking AMPA receptors not only at synapses, but also at extrasynaptic sites. Neurons therefore appear to be actively enhancing Ca2+ entry, possibly as a compensatory mechanism in response to a prolonged Ca2+ deficit. To test whether the homeostatic response may, at least in part, be mediated by internal Ca2+ stores, we depleted endoplasmic reticulum (ER) Ca2+ stores by using the Sarco/endoplasmic reticulum Ca2+ ATPases (SERCA) pump blocker cyclopiazonic acid (CPA) for a prolonged period. Interestingly, we have found that prolonged Ca2+-store depletion leads not only to an increase in synaptic strength per se, but also a cell-wide increase in synaptic Ca2+-permeable GluA2-lacking AMPARs. This increase in Ca2+ influx following periods of inactivity is conceptually highly reminiscent of a store-operated response, whereby cells re-establish their calcium levels following Ca2+ store depletion using cell surface Ca2+ channels. Our results suggest that neurons use synaptic receptors as means to regulate store Ca2+ levels, thus significantly expanding our understanding of the repertoire used by neurons to modulate cellular excitability.
Keywords: Store-Operated Responese; Homeostatic Synaptic Plasticity; AMPA Receptors; Endoplasmic Reticulum Calcium Stores; Endoplasmic Reticulum